2018
DOI: 10.1002/ecy.2400
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity‐ecosystem functioning relationships in a long‐term non‐weeded field experiment

Abstract: Many grassland biodiversity experiments show a positive relationship between biodiversity and ecosystem functioning, however, in most of these experiments plant communities are established by sowing and natural colonization is prevented by selective weeding of non-sown species. During ecosystem restoration, for example on abandoned fields, plant communities start on bare soil, and diversity is often manipulated in a single sowing event. How such initial plant diversity manipulations influence plant biodiversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 61 publications
4
34
4
Order By: Relevance
“…In contrast to species composition, trait composition did not differ between GWs for both sown and spontaneous species. This finding is consistent with previous studies on experimental plant community assembly (Fukami et al ; Li & Shipley ; Veen et al ) that reported an increasing dissimilarity in species composition (divergence) and an increasing similarity in mean trait composition (convergence) among sites, with increasing restoration age. In fact, in both GWs, vegetation was generally dominated by acrocarpous, turf‐forming mosses.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to species composition, trait composition did not differ between GWs for both sown and spontaneous species. This finding is consistent with previous studies on experimental plant community assembly (Fukami et al ; Li & Shipley ; Veen et al ) that reported an increasing dissimilarity in species composition (divergence) and an increasing similarity in mean trait composition (convergence) among sites, with increasing restoration age. In fact, in both GWs, vegetation was generally dominated by acrocarpous, turf‐forming mosses.…”
Section: Discussionsupporting
confidence: 93%
“…This contrasts with real‐world situations, and both theoretical (e.g. Leibold, Chase & Ernest, ) and empirical studies (Petermann et al, ; Veen, van der Putten & Bezemer, ) suggest that BEF relationships might be weaker in open communities, in part because species‐poor communities tend to get invaded by species that increase their biomass production. Third, in naturally assembled communities, there can be feedbacks from ecosystem functions to biodiversity (Grace et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…This is based on evidence that the effects of introducing species at the beginning of secondary succession can be long‐lasting (Veen et al. ), and in this system, the assemblage of species that are able to successfully colonize an area after a fire depends on their abilities to compete for moisture and tolerate drought (Meyer ).…”
Section: Introductionmentioning
confidence: 99%
“…Our fourth hypothesis was that temperature, vapor pressure deficit, and precipitation around the time of the fire would exert a lasting influence over post-fire community composition and diversity. This is based on evidence that the effects of introducing species at the beginning of secondary succession can be long-lasting (Veen et al 2018), and in this system, the assemblage of species that are able to successfully colonize an area after a fire depends on their abilities to compete for moisture and tolerate drought (Meyer 1994).…”
Section: Introductionmentioning
confidence: 99%